Effect of negative-pressure wound therapy on the circulating number of peripheral endothelial progenitor cells in diabetic patients with mild to moderate degrees of ischaemic foot ulcer. (August 2019) - Mu, Shichang; Hua, Qiaoqiao; Jia, Yangyang; Chen, Ming-Wei; Tang, Yizhong; Deng, Datong; He, Yong; Zuo, Chunlin; Dai, Fang; Hu, Honglin
Objective: To investigate the effect of negative-pressure wound therapy (NPWT) on the circulating number of endothelial progenitor cells (EPCs) in diabetic patients with mild to moderate degrees of ischemic foot ulcer. Methods: We selected 84 diabetic patients who had a foot ulcer with a duration of at least four weeks and who had an ankle-brachial index of 0.5–0.9. Patients were assigned to one two groups according to 2:1 randomization: NPWT group ( n = 56) and non-NPWT (patients who did not receive NPWT) group ( n = 28). The control group (NC group) was composed of 18 patients who had normal glucose tolerance and lower extremity ulcer without arteriovenous disease. NPWT was performed on the ulcer after debridement for one week for patients in both the NPWT group and the NC group, and the patients in the non-NPWT group received conventional treatment process. The circulating number of EPCs was measured before and after various treatments, and the factors influencing their changes were analysed. Results: After NPWT, the circulating number of EPCs significantly increased in both the NPWT group and the NC group ((85.3 ± 18.1) vs. (34.1 ± 12.5)/10 6 cells; (119.9 ± 14.4) vs. (66.1 ± 10.6)/10 6 cells, both P < 0.05). In contrast, the circulating number of EPCs had no significant change in the non-NPWT group ((45.2 ± 19.4) vs. (34.7 ± 16.8)/10 6 cells, P > 0.05). In addition, the circulating levels of vascular endothelial growth factor (VEGF) and the protein expressions of VEGF and stromal cell-derived factor-1α (SDF-1α) in the granulation tissue significantly increased after NPWT in both the NPWT and the NC group, but there was no significant change in the non-NPWT group. Compared with the non-NPWT group, the changes in VEGF and SDF-1α levels in the sera and granulation tissue were all significantly higher in both the NPWT and NC groups ( P < 0.05, P < 0.01, respectively). There was no significant difference in changes in the circulating number of EPCs in the peripheral blood and levels of VEGF and SDF-1α in the sera and granulation tissue between the NPWT and NC groups. Correlation analysis showed that the change in the circulating number of EPCs was correlated with the changes of VEGF and SDF-1α levels in the sera and granulation of the NPWT and NC groups ( P < 0.05). Conclusion: NPWT may increase the circulating number of EPCs in diabetic patients with mild to moderate ischaemic foot ulcer as in non-diabetic controls, which may be attributed to the upregulation of systemic and local VEGF and SDF-1α levels.